High-amylose starch as a new ingredient to balance nutrition and texture of food. (May 2018) - Zhong, Yuyue; Zhu, Heyuan; Liang, Wenxin; Li, Xu; Liu, Linsan; Zhang, Xudong; Yue, Huifen; Xue, Jiquan; Liu, Xingxun; Guo, Dongwei
Abstract: Starch can provide food (such as cake) with a good texture. However, starch also causes the postprandial glycaemic response, which leads to Type-2 diabetes and cardiovascular diseases. In this study, we developed high-amylose starch as a new ingredient. The molecular structure of high-amylose maize starch (HAMS) was also studied to explore the effects of HAMS on the physicochemical, digestion and texture properties of high-amylose maize flour cakes (HAMFCs). The results showed the small molecular size, low amounts of short amylopectin chains, and high amounts of long amylopectin chains and amylose chains of HAMS are helpful to understand the texture (the increase in hardness, cohesiveness, chewiness and resilience and the decrease in springiness) and digestion (the increase in SDS and RS and the decrease in RDS) properties, and the formation of V-type crystalline structure in HAMFCs. Special molecule structure of HAMS and V-type crystalline are the main reason for the improvement of RS in HAMFCs. Sensory evaluation showed that HAMFCs would be accepted by customers and 20% HAMF addition is the best scheme. In sum, the molecular structure of HAMS helps understand the quality of HAMFCs; and HAMFCs could be developed as novel food with a higher RS and acceptable sensory attributes. Highlights: High amylose starch as a new ingredient was used in cakes. The molecular structure was characterized by SEC. High amylose maize starch increases the resistant starch in cakes. 20% High amylose maize starch were accepted by customers.